Constructing a hexagonal copper-coin-shaped NiCoSe2@NiO@CoNi2S4@CoS2 hybrid nanoarray on nickel foam as a robust oxygen evolution reaction electrocatalyst. Issue 38 (20th September 2018) - Xu, Zhoufeng; Pan, Hailong; Lin, Yu; Yang, Zhi; Wang, Jinlei; Gong, Yaqiong
Abstract : The as-obtained hexagonal copper-coin-shaped NiCoSe2 @NiO@CoNi2 S4 @CoS2 electrode can serve as a high-performance electrocatalyst for the oxygen evolution reaction under electrochemical reaction conditions. Abstract : Employing high efficiency, earth-abundant and non-noble metals for the oxygen evolution reaction (OER) is of prime importance but still challenging. Herein, the in situ growth of hexagonal copper-coin-shaped NiCoSe2 @NiO@CoNi2 S4 @CoS2 on NF was successfully achieved via a simple and mild hydrothermal and calcination method. During the calcination process, the NiCo precursor was calcined using selenium powder as the Se source firstly and then using sublimed sulfur as the S source. The as-synthesized NiCoSe2 @NiO@CoNi2 S4 @CoS2 /NF exhibited excellent electrocatalytic activity for the oxygen evolution reaction (OER) with a lower overpotential of 310 mV@30 mA cm −2 . The better electrocatalytic activity of the electrocatalyst is associated with the well-defined hexagonal nano-copper-coin-shaped structure, great intrinsic electrocatalytic activity and synergetic effects among NiCoSe2, NiO, CoNi2 S4 and CoS2 . In addition, the as-obtained NiCoSe2 @NiO@CoNi2 S4 @CoS2 /NF catalyst could be used as both the cathode and anode in a two-electrode water splitting cell, which can deliver a current density of 10 mA cm −2 at a cell voltage of 1.583 V. The electrode also shows good water splitting durability over 24 h with negligible degradation. The great OER performance and outstanding stability indicated that NiCoSe2 @NiO@CoNi2 S4 @CoS2 /NF may work as a promising OER electrocatalyst.